Honour Killings in Pakistan: A Cultural Crime Mislabelled as Religious Practice - Bukhari, Dr. Syed Hamid Farooq; Bukhari, Dr. Syed Hamid Farooq (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Honour killings in Pakistan represent a deeply rooted cultural pathology masquerading as religiously sanctioned justice. Each year, hundreds of women—and occasionally men—are murdered by family members under the pretext of preserving familial "honour," particularly in cases involving alleged moral transgressions. While proponents often appeal to Islamic principles or tribal customs to legitimize these acts, such justifications reflect a gross misinterpretation of both Islamic law (Sharīʿah) and the moral ethos of the Qur’an and Sunnah. This article offers a comprehensive postdoctoral-level critique of honour killings, exploring them not as isolated criminal incidents but as systemic violations of human rights and divine justice. The study deconstructs the false theological and jurisprudential claims used to validate honour-based violence, drawing upon classical Islamic legal sources, contemporary fatwas, and the prophetic model of mercy, restraint, and due process. It further situates honour killings within broader sociological frameworks—examining the intersections of tribal patriarchy, state legal lacunae, and social stigma that perpetuate silence and impunity. Through critical analysis of legal statutes, court cases, and cultural narratives, the article underscores the urgency of reclaiming Islamic ethics as a means of dismantling the cultural scaffolding that enables honour crimes. Finally, the study proposes a multi-sectoral reform strategy encompassing legal reform, religious reeducation, survivor protection, and theological advocacy. Rooted in the Islamic principles of ʿadl (justice), karāmah (dignity), and ḥifẓ al-nafs (preservation of life), the article calls for a unified religious and legal stance to abolish this morally and theologically indefensible practice.